Optimization of Parameters Affecting Bioethanol Production from Oil Palm Frond Juice by Saccharomyces cerevisiae - Siti Hajar, Mat Zani; Mior Ahmad Khushairi, Mohd Zahari; Nina Suhaity, Azmi (2015)
Oil palm frond (OPF) juice has been identified as a good candidate to replace commercial sugars for the production of vale-added products such as poly(3-hydroxybutyrate), P(3HB) and bioethanol. The aim of this research was to investigate the effect of sterilization, temperature, initial pH medium and agitation speed on the production of bioethanol in shake flasks experiment using Saccharomyces cerevisiae Kyokai No. 7. One-factor-at time (OFAT) method was employed to screen the best condition of parameters which affecting the production of bioethanol.